Human Mesenchymal Stromal Cell (MSC) Characteristics Vary Among Laboratories When Manufactured From the Same Source Material: A Report by the Cellular Therapy Team of the Biomedical Excellence for Safer Transfusion (BEST) Collaborative - Stroncek, David F.; Jin, Ping; McKenna, David H.; Takanashi, Minoko; Fontaine, Magali J.; Pati, Shibani; Schäfer, Richard; Peterson, Emily; Benedetti, Eric; Reems, Jo-Anna (Frontiers in Cell and Developmental Biology, 2020)
Background: Culture-derived mesenchymal stromal cells (MSCs) exhibit variable characteristics when manufactured using different methods and different source materials. The purpose of this study was to assess the impact on MSC characteristics when different laboratories propagated MSCs from cultures initiated with BM aliquots derived from the same donor source material . Methods and Methods: Five aliquots from each of 3 different BM donors were distributed to 5 independent laboratories. Three laboratories plated whole BM and 2 laboratories a mononuclear BM cell fraction. Four laboratories cultured in media supplemented with fetal bovine serum (FBS) and 1 laboratory used human platelet lysate (hPL). Initial cell seeding densities (i.e. P0) ranged from 19.7x103/cm2-282 x103/cm2 and for second seeding (i.e. P1) 0.05x103-5.1x103 cells/cm2. Post-thawed MSCs from each laboratory were analyzed for cell viability, immunophenotype, tri-lineage differentiation, fibroblast colony-forming units (CFU-F), gene expression, and immunosuppressive activity. Results: Transit times from BM collection to receipt by laboratories located in the United States ranged from 16.0-30.0 hrs and from 41.5-71.5 hrs for a laboratory in Asia. Post-thaw culture derived MSCs exhibited viabilities that ranged from 74-92%, 61-96%, and 23-90%. CFU-F activity per 200 MSCs plated averaged 45.1±21.4, 49.3±26.8 and 14.9±13.3, respectively. No substantial differences were observed in immunophenotype, and immunosuppressive activities. Global gene expression profiles of MSCs revealed transcriptome differences due to different inter-laboratory methods and to donor source material with the center effects showing greater molecular differences than source material. Conclusions: Functional and molecular differences exist among MSCs produced by different centers even when the same BM starting material is used to initiate cultures. These results indicated that manufacturing of MSCs by 5 independent centers contributed more to MSC variability than did the source material of the BM used in this study. Thus, emphasizing the importance of establishing worldwide standards to propagate MSCs for clinical use.